Pengaruh Penggunaan Pupuk pada Produksi Cabai Keriting di Desa Toriki Kecamatan Anggaberi Kabupaten Konawe - Sarty Syarbiah (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2024)
This study aims to determine the purpose of this study is to determine the Effect of Fertilizer Use on the Production of Curly Chili in Toriki Village, Anggaberi District, Konawe Regency. The location of this study is in Toriki Village, Anggaberi District, Konawe Regency. The number of samples in this study was 12 farmers. To complete the research objectives using Multiple Linear Regression analysis. Based on the results of the study, it shows that the Use of SP 36 Fertilizer, manure, NPK Pelangi fertilizer and NPK Mutiara fertilizer have a positive and significant effect on the Production of Curly Chili in Toriki Village, Anggaberi District, Konawe Regency. This can be seen from the value of the use of SP 36 fertilizer (X1) of 2.654 with a significance level of t of 0.025 which is smaller than α = 5%, where (0.025 <0.05). The use of manure (X2) is 3.112 with a significance level of t of 0.012 smaller than α = 5%, where (0.012 < 0.05). The use of NPK Pelangi fertilizer (X3) is 2.224 with a significance level of t of 0.011 smaller than α = 5%, where (0.011 < 0.05). The use of NPK Mutiara fertilizer (X4) is 3.143 with a significance level of t of 0.035 smaller than α = 5%, where (0.035 < 0.05).